2016
DOI: 10.1007/s13300-016-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

Peer-to-Peer, Interactive GP Education can Reduce Barriers to Best Practice in Diabetes Management

Abstract: IntroductionPerceived difficulties in initiating insulin in patients with type 2 diabetes (T2D) may prevent many general practitioners (GPs) from using insulin even when recommended in guidelines. This paper describes a Royal Australian College of General Practitioners accredited education program on starting insulin in T2D, and its impact on GPs’ attitudes and behavior.MethodsA faculty comprising GPs with diabetes expertise, Credentialed Diabetes Nurse Educators, and endocrinologist developed and implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…33 Evidence has shown that appropriate training of community health workers and nurses can effec-Nurse Management of Hypertension in Kenya -Vedanthan et al tively increase hypertension knowledge and clinical skills. By empowering these health care professionals through appropriate hypertension training, it is possible to increase confidence, 34 consequently creating an improved patient experience and possibly improved clinical outcomes.…”
Section: Nurse Management Of Hypertension In Kenyamentioning
confidence: 99%
“…33 Evidence has shown that appropriate training of community health workers and nurses can effec-Nurse Management of Hypertension in Kenya -Vedanthan et al tively increase hypertension knowledge and clinical skills. By empowering these health care professionals through appropriate hypertension training, it is possible to increase confidence, 34 consequently creating an improved patient experience and possibly improved clinical outcomes.…”
Section: Nurse Management Of Hypertension In Kenyamentioning
confidence: 99%
“…After reading the full text, 13 articles were selected for the final systematic review. Eleven were quantitative [six randomized controlled studies (914), one non–randomized community intervention (15), three pre- and post-intervention analysis (1618), one cross-sectional (19)], one was a qualitative study (20), and one used mixed methods (21). The main characteristics of the studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Three pre- and post-intervention studies focused on the management of chronic hepatitis B (17), diabetes (16), and radiation oncology (18) (Table 1). Educational interventions included workshops with interactive peer-to-peer group learning (16) or interactive sessions with case discussions (18) and the distribution of treatment guidelines delivered by nurses (17).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations